Democracia deliberativa em Habermas : abordagem do tema no Brasil (2000-2015) e contribuições para a educação - Pinheiro, Edneia Virginia (2017)
Habermas's philosophical-political work occupies centrality in contemporary democratic theory as a discourse of justification of the deliberative conception of democracy. Assuming a political society capable of establishing normative principles with a view to legitimizing the rule of law, Habermas presents the communicative process of formation of opinion and will as the most important means for the discursive rationalization of the decisions of an administration linked to law. The subjects, as legal partners, act in the elaboration of the legitimate right, of which they are authors and recipients. As a mediator between the world of life and the system, modern law appears as a means to solve the problems of social coordination in a plural society. Understanding that the Habermas' democratic theory is capable of bringing important contributions to reflections in the educational field, we seek to know what use has been made of it in studies and research developed in Brazil and the relevance of its use in the area of education, especially for the democratic management of the school. To answer these questions, we opted for the development of a bibliographical research that had as its source articles published in periodicals. We chose for the bibliographic survey the Periódicos CAPES portal and the SciELO database. From the analysis of articles from nine different areas of knowledge, we sought to identify how deliberative democracy has been approached in studies and research developed in Brazil, the main notes present in articles, the most frequently treated subjects and those that are in apparent emergencies. Completed the analysis of this material, we identified the need to conduct a survey of complementary readings in the area of education, aiming to better establish the overview of discussions that involve the subject. We identify then the ongoing discussions in other areas of knowledge that may contribute to or corroborate discussions in the area of education and democratic school management. Confirming the thesis presented by this search, we conclude that Habermas' interpretation of capitalist society, as a system and world of life, provides us with an important support for the analysis of the problems faced by education, for understanding the relevance of the establishment of discursive processes in school, aiming at the implementation of democracy in its space, the reversal of the process of colonization of the world of life and the formation of participatory, critical and emancipated citizens.